PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DALAM MENINGKATKAN HASIL BELAJAR SISWA POKOK BAHASAN ARITMATIKA SOSIAL SISWA KELAS VIIC SMPN 5 JEMBER SEMESTER GANJIL TAHUN AJARAN 2012/2013 - Ristiana, Neni; Suharto, S; Trapsilasiwi, Dinawati (KadikmA, 2012)
Abstract. This research used Cooperative Learning models type Cooperative Integrated Reading and Composition (CIRC). This model has seven principal elements. The purpose of this research was to increase studentsâ activities and learning result. This research was a Classroom Actions Research (CAR) in two learning cycles, there were two meetings in each cycle. Our topic was about Social Arithmetic. The research methods were documentation, observation, test and interview. The data analyzed are teacherâs activities, the studentsâ activities and studentsâ test result. The Final result of the studentsâ activities and the studentsâ test result in this research from the first cycle to the second cycle increased. The studentsâ tes result increases 15,79%. Key Words : CooperativeÂ  learning models type Cooperative Integrated Reading and Composition (CIRC), studentsâ test result, studentsâ activities.